Penyuluhan Bagi Remaja Masjid Baiturrohman Sumbersari Tentang Covid-19 - Arif Thohari; Muhammad Faiz Amiruddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Real Work Lecture (KKN) is a community service activity in a certain area as an implementation of Tri Darma college. KKN activities aim to provide field experience to students about the condition of society directly and also to form an independent attitude and responsibility in carrying out KKN activities. The implementation of KKN starts from the date until August 27, 2020 in the baiturrohman Sumbersari Mosque, Kencong Village, Kepung District, Kediri Regency. The program conducted at Baiturrohman Sumbersari Mosque in the form of socialization activities to mosque youth about Covid-19 starts from its understanding, symptoms that occur, and how to prevent it. In general, KKN activities carried out in baiturrohman Sumbersari Mosque, Kencong Village, Kediri District, went well because the response of mosque youth was also good. The implementation of KKN programs is expected to benefit the community, especially mosque youth in order to implement government programs in the current pandemic period by always complying with established health protocols.